circSPECC1 Promotes Proliferation and Migration of LNCaP Prostate Cancer Cells by Affecting Their Epithelial-Mesenchymal Transition - Fangmei Xie; Jian Shen; Zeping Han; Wenfeng Luo; Liyin Liao; Jinhua He (Journal of Immunology Research)
Objective. To determine the effects of circSPECC1 (hsa_circ_0000745) on the proliferation and migration of LNCaP prostate cancer cells and to explore the potential molecular mechanism. Methods. Stable circSPECC1 shRNA-expressing and circSPECC1-overexpressing LNCaP cell lines were constructed, and relative gene expression levels were determined by RT-PCR. MTT and clonogenic assays were used to assess proliferative ability while a scratch test was used to analyze cell migration. Western blotting was used to determine protein expression levels. The effects of circSPECC1 on the proliferation of LNCaP prostate cancer cells were observed in vivo. Results. circSPECC1 was found to be derived from the SPECC1 (sperm antigen with calponin homology and coiled-coil domains 1) parent gene and to form a loop. Overexpression of circSPECC1 promoted the proliferation and migration of the LNCaP cells, whereas decreased expression of circSPECC1 inhibited these properties. Overexpression of circSPECC1 promoted the expression of MMP-2, MMP-9, VEGF, vimentin, and N-cad but downregulated the expression of E-cad. Decreased expression of circSPECC1 inhibited the expression of MMP-2, MMP-9, VEGF, vimentin, and N-cad but increased the expression of E-cad. Conclusion. circSPECC1 promotes cell proliferation and migration by affecting the epithelial-mesenchymal transition of LNCaP prostate cancer cells.